KONVERSI AGAMA DALAM MASYARAKAT PLURAL: UPAYA MEREKAT PERSAUDARAAN ANTARUMAT BERAGAMA DI INDONESIA - Lukita Fahriana; Lufaefi Lufaefi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
Indonesia is a country that is inhabited by various religious adherents. Not a little diversity that led to conflicts. One of the factors arising from the conflict is because of the conversion of religions, especially if done by people of Islam who moved to other religion in overt. Conversion is seen as apostasy, the consequence of which is sin and must be killed. In the conversion of religion, change or is not merely due to matters of belief, or degrading religion, but many factors cause it, such as environmental factors, social relations, psychology, and even because the factor of Divine guidance. In a pluralistic society, the existence of religious conversion can glue brotherhood between religious communities. Therefore, the conversion of religion can shape one's thoughts to accept and appreciate the religion of others more openly in many perspectives.